STUDIES ON THE ANTIBACTERIAL ACTION OF THE SULFONAMIDE DRUGS : II. THE POSSIBLE RELATION OF DRUG ACTIVITY TO SUBSTANCES OTHER THANp-AMINOBENZOIC ACID - Wood, W. Barry (The Rockefeller University Press, 1942)
1. In cultures of Staphylococus aureus in a synthetic medium nicotinamide and cozymase were shown to block the bacteriostatic action of chemically unrelated sulfonamide drugs as well as the chemically related compound sulfapyridine. The antibacterial properties of organic dyes totally unrelated to the sulfonamide compounds (methylene blue and thionine) were also nullified by the addition of cozymase to the culture medium. 2. The antagonistic action of the pyridine-containing coenzyme, cozymase, was found, by quantitative study, to be no greater against sulfapyridine than against other structurally dissimilar sulfonamide compounds. 3. The antidrug effects of nicotinamide and cozymase in staphylococcus cultures were observed to be directly proportional to their ability to stimulate the growth of the organism in the synthetic medium. When tested in cultures of B. coli in which they failed to accelerate bacterial growth, these same substances failed to influence the bacteriostatic action of the sulfonamide drugs. 4. The in vitro action of the coenzyme, cocarboxylase, as measured in the Warburg respirometer, was shown to be unaffected by the chemically related drug, sulfathiazole, even when the latter was present in great excess. The above observations fail to support the theory that sulfapyridine, sulfathiazole, and sulfadiazine prevent bacterial growth by interfering with the functioning of the chemically related coenzymes, cozymase, and cocarboxylase. The mode of action of sulfanilamide and its more common derivatives is discussed in the light of these observations, and a tentative theory is offered to explain the differences in bacteriostatic potency exhibited by the various sulfonamide compounds.